2020
DOI: 10.30544/587
|View full text |Cite
|
Sign up to set email alerts
|

Arc Plasma Deposition of TiO2 Nanoparticles from Colloidal Solution

Abstract: Surface modifications of metallic biomaterials can in great merit, improve the properties of the hard-tissue implants and in that way contribute to the success of the surgical implantation process. Coating deposition stands out as one of the many surface-modifying techniques that can be used to improve implant surface properties and, in turn, induce successful osseointegration. Deposition of the TiO2 layer on the surface of the metallic implants has a great potential to enhance not only their osseointegration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Cathodic arc plasma deposition (CAPD) is categorized as a physical vapor deposition technique. 28,29 During CAPD, the target material is converted to plasma via arc discharge, and the generated plasma is fully ionized with very energetic ions. The energetic condensation of ions on the substrate from the cathodic arc plasma promotes the formation of flat, dense, well-adherent films.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cathodic arc plasma deposition (CAPD) is categorized as a physical vapor deposition technique. 28,29 During CAPD, the target material is converted to plasma via arc discharge, and the generated plasma is fully ionized with very energetic ions. The energetic condensation of ions on the substrate from the cathodic arc plasma promotes the formation of flat, dense, well-adherent films.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this synthetic limitation, few mechanistic studies regarding Si/sulfide electrolyte interfaces are reported, even in thin-film systems. Cathodic arc plasma deposition (CAPD) is categorized as a physical vapor deposition technique. , During CAPD, the target material is converted to plasma via arc discharge, and the generated plasma is fully ionized with very energetic ions. The energetic condensation of ions on the substrate from the cathodic arc plasma promotes the formation of flat, dense, well-adherent films. , Furthermore, the immobilization of the deposited species, owing to rapid energy loss, may suppress atomic diffusion into the substrate bulk .…”
Section: Introductionmentioning
confidence: 99%